Bacteriocinogenic potential of lactic acid bacteria isolates from artisanal fermented meat products - Castilho, Natália Parma Augusto (2018)
The aim of the study was isolate and characterized lactic acid bacteria (LAB) from artisanal fermented meat products through phenotypic and genotypic methodologies, searching for the selection of isolates with bacteriocinogenic potential. LAB isolates were obtained from artisanal fermented meat products and were characterized to their bacteriocinogenic activity; after isolation and identification were obtained 5 different isolates: Lactobacillus curvatus 12 and 36; Lactococcus garvieae 32 and Weissella viridescens 23 and 31 and the detection of bacteriocins related genes were performed; L. curvatus 12 and 36 e W. viridescens 23 were selected for the other analysis to evaluate the bacteriocinogenic potential. The selected isolates showed distinct growth and bacteriocin production was more evident in L. curvatus 12 and W. viridescens 23. The bacteriocins produced were adsorbed by the producing strains at different levels. Partially purified bacteriocins maintained their inhibitory activity after elution with 60% isopropanol. Cell lysis patterns were similar for all isolates tested. Detection of β-galactosidase indicated destabilization of the cell membrane permeability of the isolated BAL. The bacteriocins produced by L. curvatus 12 were purified by HPLC and four different peptide sequences were identified. The selected BAL isolates were able to produce bacteriocins with high inhibitory activity against L. monocytogenes, indicating their potential application in the food industry as bioconservatives. For the evaluation of the presence of virulence genes, resistance to antibiotics and probiotics, the five isolates previously identified were used. All isolates tested were positive for mub, while EF226-cbp, EF1249-fbp and EF2380-maz were detected in at least one isolate; none isolated showed map, EFTu or prgB. The isolates tested presented variable results in relation to the virulence genes and no isolates showed the genes gelE, cylA, efsA, cpd, int-Tn or sprE. Antibiotic resistance genes were also detected at different patterns. LAB isolates presented some beneficial aspects besides the production of bacteriocins, but the presence of virulence genes and resistance to antibiotics is a problem when using these isolates as starter or bioconservative cultures in foods. Considering the inhibitory potential of these strains, an alternative would be the use of their bacteriocins after semi-purification or purification procedures. Fresh sausage was prepared and inoculated with different combinations of L. curvatus 12 (bacteriocinogenic BAL), L. sakei ATCC 15521 (non bacteriocinogenic BAL), L. monocytogenes, nisin and partially purified bacteriocin produced by L. curvatus 12 and stored at 7 ° C for 10 days. Microbiological analyzes were performed on days 1, 4, 7 and 10 and physical-chemical analyzes (control) on days 1 and 10. In general, LAB counts did not show significant differences between treatments and throughout the storage period (p> 0.05). The counts of L. monocytogenes in fresh sausage inoculated with the pathogen and the bacteriocinogenic LAB varied from 1.0 to 2.0 log CFU/g, being significantly different from the sausage inoculated with only L. monocytogenes (p < 0.05). Nisin and partially purified bacteriocin also determined a reduction in the counts of L. monocytogenes when compared to the treatment that was inoculated only the pathogen, ranging from 1.0 to 3.0 log CFU/g (p> 0.05). These results indicate that the bacteriocinogenic LAB was able to determine a significant reduction in the count of L. monocytogenes in fresh sausage stored at 7 ° C.